Kajian Simbolik dan Ikonik dalam Kumpulan Cerpen Orang-Orang Bloomington Karya Budi Darma - Gunawan, Iqbal Nur; Wadji, Wadji; Suryantoro, Suryantoro (Universitas Negeri Padang, 2025)
Budi Darma's short story collection, Orang-Orang Bloomington, contains stories set in American culture while still addressing common human anxieties. Budi Darma's writing style, which tends toward the absurd and reflective, creates a complex narrative experience. The objectives of this study include analyzing representation and uncovering the meaning of symbols and icons in Orang-Orang Bloomington. The research data consist of narrative excerpts, dialogue, and descriptions containing symbols and icons. Supporting instruments, such as data tables, were used to facilitate the classification and analysis of signs. The data collection process involved several stages: reading all short stories in their entirety, identifying sections of the text containing semiotic signs, noting relevant quotations, grouping data based on sign types according to Peirce's classification (icons and symbols), and compiling selected quotations for further analysis. The results show that symbols depict alienation, inner emptiness, and the characters' identity crises, and form deeper meanings within the narrative structure. This finding confirms that the use of semiotic signs in short stories not only enriches the narrative, but also reflects existential themes such as social alienation and the search for the meaning of life